'Eating with One Spoon': Zoning, Power Rotation and Political Corruption in Nigeria. Issue 1 (2nd January 2016) - Ololajulo, Babajide Olusoji
ABSTRACT: The practice of liberal democracy in Nigeria is overshadowed by the clamours for political zoning and other power-sharing arrangements as mechanisms for ethno-regional balancing. A few scholarly commentaries have alluded to the capacity of such informalities for conflict mitigation and consensus formation in plural societies. Drawing motivation from a traditional paradigm of power rotation among the Ilaje of Ondo state, Nigeria, this article based on a qualitative study, examines how ideas and practices of zoning and rotational access to political power intersect with identity politics, corruption, and the ideals of liberal democracy in Nigeria. The article affirms that the prevalence of zoning and power rotation as forms of political practices across Nigeria, and the discourse built around the two, point toward a national and local appropriation and accommodation of the concepts. It argues that though the practices have the capacity for maintaining peaceful political order, they have occurred more as an elites' strategy to negotiate continued participation in the political process and access to the national wealth. The article, therefore, concludes that political turn-taking exemplifies 'a social mechanism of corruption' and a perverted form of liberal democracy.